Evaluating Curriculum Viability in Dental Education: A Mixed-Methods Study at HITEC Institute of Medical Science - Shaukat, Fatima; Sultan, Rizwan; Omer, Umme Ammarah; Tassaduq, Irum; Ambreen, Salma; Zakria, Naila (Pakistan Armed Forces Medical Journal, 2025)
Objective: To identify key areas where the curriculum may be lacking, thereby providing insights for curriculum enhancement efforts. Study Design: Mixed method study – explanatory sequential type. Place and Duration of Study: HITEC Institute of Medical Sciences, Heavy Industries Taxila Cantt, Pakistan, from May to Jun 2024. Methodology: A validated questionnaire was distributed to 75 faculty members at HITEC Dental College. Categorical data analysis was conducted using frequencies and percentages of participant’s answer. In next phase of study, a Focus group discussion was done involving 8 faculty members to discuss results of first phase allowing for a comprehensive assessment of faculty perceptions regarding significant curricular inhibitors. The solutions provided by the faculty to overcome these inhibitors were recorded and described in the study. Results: Analysis of 50 responses revealed that the overall educational program was perceived positively and aligned with institutional goals. Five out of the 25 items of the questionnaire were highlighted as ineffective. Two items were related to social interaction, one related to disciplinary culture, institutional policies and faculty involvement. Thematic analysis in the focus group discussions with eight senior faculty members supported these findings and provided deeper insights. Conclusion: This study highlighted key inhibitors to curricular success of the college and targeted strategies to overcome these inhibitors. By conducting similar researches frequently and in other institutions, effectiveness of curriculum can not only be assessed but also improved.